Insulin and GSK3β-inhibition abrogates the infarct sparing-effect of ischemic postconditioning in ex vivo rat hearts. (4th May 2017) - Helgeland, Erik; Wergeland, Anita; Sandøy, Rune M.; Askeland, Maren; Aspevik, Anne; Breivik, Lars; Jonassen, Anne K.
Abstract: Objectives. Pharmacological treatment of reperfusion injury using insulin and GSK3β inhibition has been shown to be cardioprotective, however, their interaction with the endogenous cardioprotective strategy, ischemic postconditioning, is not known. Design. Langendorff perfused ex vivo rat hearts were subjected to 30 min of regional ischemia and 120 min of reperfusion. For the first 15 min of reperfusion hearts received either vehicle (Ctr), insulin (Ins) or a GSK3β inhibitor (SB415286; SB41), with or without interruption of ischemic postconditioning (IPost; 3 × 30 s of global ischemia). In addition, the combination of insulin and SB41 for 15 min was assessed. Results. Insulin, SB41 or IPost significantly reduced infarct size versus vehicle treated controls (IPost 33.5 ± 3.3%, Ins 33.5 ± 3.4%, SB41 30.5 ± 3.0% vs. Ctr 54.7 ± 6.8%, p < 0.01). Combining insulin and SB415286 did not confer additional cardioprotection compared to the treatments given alone (SB41 + Ins 26.7 ± 3.5%, ns). Conversely, combining either of the pharmacological reperfusion treatments with IPost completely abrogated the cardioprotection afforded by the treatments separately (Ins + IPost 59.5 ± 3.4% vs. Ins 33.5 ± 3.4% and SB41 + IPost 50.2 ± 6.6% vs. SB41 30.5 ± 3.0%, both p < 0.01), and was associated with blunted Akt, GSK3β and STAT3 phosphorylation. Conclusion. Pharmacological reperfusion treatment with insulin and SB41 interferes with the cardioprotection afforded by ischemic postconditioning.